2021
DOI: 10.3390/ijerph18062817
|View full text |Cite
|
Sign up to set email alerts
|

Association between Viral Infections and Risk of Autistic Disorder: An Overview

Abstract: Autism spectrum disorder (ASD) is a neurodevelopmental condition of the central nervous system (CNS) that presents with severe communication problems, impairment of social interactions, and stereotypic behaviours. Emerging studies indicate possible associations between viral infections and neurodegenerative and neurobehavioural conditions including autism. Viral infection during critical periods of early in utero neurodevelopment may lead to increased risk of autism in the offspring. This review is aimed at hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 139 publications
0
34
0
Order By: Relevance
“…The MIA model was developed based on the observation that infection during pregnancy is linked to ASD ( Atladottir et al, 2010 ; Zerbo et al, 2015 ; Al-Haddad et al, 2019 ). Outbreaks of several viruses, such rubella and influenza, have been documented to be associated with increased numbers of individuals with ASD ( Zerbo et al, 2013 ; Shuid et al, 2021 ). Consistent with these findings, the MIA model uses the injection of a toll-like receptor (TLR) ligand into pregnant wild-type female mice on a specific day of gestation to induce an immune response.…”
Section: Introductionmentioning
confidence: 99%
“…The MIA model was developed based on the observation that infection during pregnancy is linked to ASD ( Atladottir et al, 2010 ; Zerbo et al, 2015 ; Al-Haddad et al, 2019 ). Outbreaks of several viruses, such rubella and influenza, have been documented to be associated with increased numbers of individuals with ASD ( Zerbo et al, 2013 ; Shuid et al, 2021 ). Consistent with these findings, the MIA model uses the injection of a toll-like receptor (TLR) ligand into pregnant wild-type female mice on a specific day of gestation to induce an immune response.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that the maternal immune response influences neurodevelopmental trajectory, altering offspring susceptibility to psychiatric illness ( al-Haddad et al., 2019 ). As suggested by the name, SARS-CoV-2 is largely defined by respiratory symptoms, lending face similarities to infections known to be associated with psychiatric illness risk ( Bordallo et al., 2020 ; Shuid et al., 2021 ). MIA via infection likely intersects with maternal stress and in the context of MIA due to SARS-CoV-2, these interacting factors are especially pertinent.…”
Section: Considerations For the Future: From Historical Epidemiology To A Present-day Pandemicmentioning
confidence: 99%
“…Studies have reported that IL-1β, IL-6 and IL-17 are key molecules for infection-induced ASD ( Al-Ayadhi and Mostafa, 2012 ; Ashwood et al 2011a , 2011b ; Shuid et al, 2021 ), being the injection of either of these cytokines in animal models sufficient to trigger ASD-like behavior ( Favrais et al, 2011 ; T. Smith et al, 2007 ). Concerning the SARS-CoV-2 infection, one recent study found a concordant profile of inflammatory markers, particularly IL-6, IL-17 and tumor necrosis factor alpha (TNF-α), in peripheral blood of pregnant women as well as in the umbilical cord blood ( Fenizia et al, 2020 ).…”
Section: Viral Infections and Neurodevelopmental Disordersmentioning
confidence: 99%